RIVAL UNDER ONE ROOF: LEGAL AND ECONOMIC PERSPECTIVES ON STATE-OWNED ENTERPRISE SUBSIDIARIES IN INDONESIA’S INTERNET SERVICE PROVIDER SECTOR - Yulidar, Ardiyantoro Muhammad (Departement of Constitutional Law UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
When public entities compete under the same state roof, the lines between national service and commercial ambition blur. In Indonesia’s internet service provider (ISP) sector, subsidiaries of state-owned enterprises (SOEs)—including ICONNET (PLN), PGNCOM (Pertamina), and JMRB (Jasa Marga) —have entered commercial markets, often overlapping with private actors. While their expansion is framed as part of national digital infrastructure development, it raises institutional and legal tensions related to role boundaries, governance neutrality, and market efficiency. This study applies a normative legal approach, supported by institutional economic theory—particularly comparative advantage and institutional specialization —to evaluate whether such activities are consistent with public mandates and regulatory frameworks. Drawing on Law No. 1/2025, Government Regulation No. 72/2016, and Government Regulation No. 46/2021, the paper identifies sectoral misalignment and structural ambiguities that threaten competitive neutrality. It concludes with policy recommendations for clarifying institutional roles, reinforcing infrastructure-sharing governance, and ensuring that public investment aligns with long-term market integrity.